Use of Rasch analysis to refine a patient-reported questionnaire on satisfaction with communication of the multiple sclerosis diagnosis. (August 2014) - Solari, A; Grzeda, M; Giordano, A; Mattarozzi, K; D'Alessandro, R; Simone, A; Tesio, L; ,
Background: The Comunicazione medico-paziente nella Sclerosi Multipla – Revised (COSM-R) is a patient self-assessed questionnaire probing the moment of multiple sclerosis (MS) diagnosis disclosure (section 1, five items) and following period (section 2, 15 items). Objectives: This study examined COSM-R dimensionality and measurement properties through Rasch analysis (partial-credit model) and proposed a revised questionnaire. Methods: Cross-sectional COSM-R data were obtained from 1068 people with MS (PwMS, 1065 questionnaires) participating in four studies (102 centres). Mean age was 40 years (range 17–73); 70% were women; 53% were from Northern, 25% from Central, and 21% from Southern Italy. Results: Unidimensionality was not confirmed for COSM-R section 1, but was for section 2 after removal of three items. The revised instrument (COSM-S, Shortened) consisted of the original five-item checklist (section 1), modified by removing the table grouping of three items, and 12 of the original 15 section 2 items, which could now be summed and transformed into an interval scale. Scores were higher for items assessing emotional satisfaction than for those assessing informational satisfaction. Conclusions: The proposed COSM-S is a composite measure of satisfaction with MS diagnosis communication with improved metric properties over the original COSM-R, and whose section 2 satisfies Rasch model expectations.